The impact of cash flow hedge accounting on future profitability and stock returns: a country comparison - Paula, Douglas Augusto de (2024)
This study analyzes the effects of cash flow hedges on future profitability and stock returns. It investigates a comprehensive sample of 44 (forty-four) countries. This works first finding is a negative and significant relationship between cash flow hedges and future profitability in every country, however, this relationship is mixed and heterogeneous among countries, which may indicate that there are various drivers of the relationship between cash flow hedges and future profitability. Secondly, it employs a three-horizon model of the effects that cash flow hedges have on stock returns which proved to be a positive and significant relationship for returns one and two years in the future. In a complementary manner, one of this studys findings is that investors interpret the gains of cash flow hedges as positive for current returns, but negative for a two-year time frame. These results present some similarities to previous studies and complement specific findings related to gains and losses that could be interpreted by investors in different ways. Also, these results are similar to Hypothesis One and are heterogeneousamong these countries. Finally, no evidence was found that countries with legal regimes presente statistically significant differences in terms of investor information regarding the immediate prices of cash flow hedges.